Optimizing performance: a holistic review of the physical, mental, and technical aspects of honing kedeng smashes - Bais, Syahril; Kiram, Phil Yanuar; alnedral, alnedral; Komaini, Anton; Sin, Tjung Hauw; Padli, Padli; Zarya, Fiky (Departement of Sports Coaching, Faculty of Sports Sciences, Universitas Negeri Yogyakarta, 2024)
This research was motivated by the problem of low level of kedeng smash ability in BBTC sepaktakraw athletes in Padang City which has not met expectations. The purpose of this study was to investigate in depth the kedeng smash ability possessed by BBTC sepaktakraw athletes in Padang City. The research method used is a descriptive type, with a population of all BBTC Sepaktakraw Club athletes in Padang City who are actively training, consisting of 16 boys and 7 girls, a total of 23 people. Samples were taken using purposive sampling techniques, so it involved ten BBTC sepaktakraw athletes from Padang City who had the role of smashers. The research instrument used is a test of kedeng's smash ability. The collected data were analyzed using frequency distribution techniques with percentage calculations (P = F/N x100%). The results of the analysis showed that the smash ability of sepaktakraw Club BBTC athletes in Padang City was in the less category. These findings provide a clear picture of the level of technical skill of the athletes, particularly in the aspect of kedeng smashes. In an effort to improve athletes' abilities, this research provides a solid foundation for the development of more targeted and effective training programs. With a deep understanding of weaknesses in kedeng's smash ability, coaches and club managers can devise more specific training strategies to improve athletes' performance. The implications of this research not only enrich the literature in the world of sepaktakraw sports, but also contribute directly to improving the achievements of BBTC Kota Padang athletes in the competition arena.